2021
DOI: 10.1186/s13046-021-02129-9
|View full text |Cite
|
Sign up to set email alerts
|

Super-enhancer-associated TMEM44-AS1 aggravated glioma progression by forming a positive feedback loop with Myc

Abstract: Background Long non-coding RNAs (lncRNAs) have been considered as one type of gene expression regulator for cancer development, but it is not clear how these are regulated. This study aimed to identify a specific lncRNA that promotes glioma progression. Methods RNA sequencing (RNA-seq) and quantitative real-time PCR were performed to screen differentially expressed genes. CCK-8, transwell migration, invasion assays, and a mouse xenograft model were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 66 publications
(38 reference statements)
2
29
0
Order By: Relevance
“…Studies have shown that in many human malignancies, including glioma, functional alterations of specific lncRNAs promote tumor formation, progression, and metastasis ( 30 ). Previously, our study found that the activation of lncRNA TMEM44-AS1 can promote malignant progression of glioma through Myc positive feedback loop ( 31 ). Tumor cells often grow in an anoxic environment with chronic ER stress, which is caused by the accumulation of misfolded and unfolded proteins in the ER under various stimuli and pathological conditions ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that in many human malignancies, including glioma, functional alterations of specific lncRNAs promote tumor formation, progression, and metastasis ( 30 ). Previously, our study found that the activation of lncRNA TMEM44-AS1 can promote malignant progression of glioma through Myc positive feedback loop ( 31 ). Tumor cells often grow in an anoxic environment with chronic ER stress, which is caused by the accumulation of misfolded and unfolded proteins in the ER under various stimuli and pathological conditions ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 97%
“…Oncogenic super-enhancers were also identified in colorectal cancer through genome-wide profiling [ 18 ]. In addition, super-enhancer was reported to play a role in glioma progression [ 19 ]. Super-enhancer was also found to be involved in squamous cell carcinoma [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Super-enhancers were found to govern PHF19 and TBC1D16 and participate in colorectal cancer tumorigenesis. In addition, super-enhancer was reported to play a role in glioma progression [ 19 ]. In glioma cells, TMEM44-AS1 activates Myc signaling, and Myc binds to the super-enhancer of TMEM44-AS1, forming a positive feedback loop.…”
Section: Introductionmentioning
confidence: 99%
“…(stimulating tumor cell proliferation, colony formation, migration and invasion [15] ) and mRNA SERPINB2…”
Section: Discussionmentioning
confidence: 99%